Medial Nasal Bone Scoring: A Novel Technique for Improving Osteotomies During Rhinoplasty. Issue 3 (September 2020) - Daraei, Paul P.; Doshi, Hardik; DeJoseph, Louis M.
Nasal bone osteotomies are commonly performed in rhinoplasty to manipulate the upper third of the nose. In patients with a dorsal hump, reduction is often performed, followed by lateral osteotomies to medialize the nasal bone complex. However, fracture patterns are often unknown in vivo. We intend to map nasal bone osteotomies and describe a novel and minimally invasive method of performing medial scoring osteotomies to improve fracture patterns and surgical speed, and decrease complications. In total, 19 formalin-fixed cadavers were dissected to reveal nasal bone architecture. The nasal dorsum (bony and cartilaginous) was reduced to form an open roof deformity. Osteotomies were then performed on all 19 specimens, followed by digital infracture. Medial scoring osteotomies were performed unilaterally, along with a lateral osteotomy. On the contralateral side, only lateral osteotomies were performed. Fracture patterns were mapped and compared. Of 19 cadaver specimens, 38 sides were examined in total: 19 sides underwent medial scoring and 19 sides served as controls. Fracture patterns were linear with less comminution on sides with medial scoring osteotomies. Sides with medial scoring osteotomies also achieved uniform closure of the open roof deformity, compared with 73% in sides without. Rocker deformity was not seen in either group. Osteotomies are integral to nasal dorsum reduction and modification of the upper third of the nose in rhinoplasty. Scoring of the medial nasal bone prior to lateral osteotomy and digital infracture allows for an increased rate of open roof closure. Furthermore, medial scoring osteotomies create smooth, linear fracture patterns that prevent bony spicules, comminution, and irregularities that may be evident in patients with thin nasal skin. Performing the medial scoring osteotomy is a fast, safe method of achieving consistent nasal bone infracture during rhinoplasty.